ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP JANGKA WAKTU PENYELESAIAN AUDIT DI BURSA EFEK INDONESIA - Sari, Indah Purnama; Effendi, Syahril (SCIENTIA JOURNAL, 2020)
This study aims to analyze whether or not there is influence, either partially or simultaneously between company size, solvency, and profitability on the period of audit completion (audit delay) in agricultural sector companies listed on the Indonesia Stock Exchange (IDX). By using the purposive sampling method as a sample technique, 10 agricultural sample companies listed on the Indonesia Stock Exchange were obtained from 2015-2019. Data analysis using multiple linear regression analysis and data processed using the SPSS version 21 program. Based on the result of this study indicate that partially company size has a negative effect on audit delay, while solvency has a positive effect on audit delay and profitability has no effect on audit delay. F test results show that simultaneous company size, solvency and profitability significantly influence audit delay with a significant value of 0,000 < 0,05.